Changes in eating in dementia. - Fairburn, C; Hope, R (1988)
Changes in eating and weight are not uncommon in dementia although they have yet to be systematically studied. These changes are of clinical importance since they can seriously affect patients' physical health and they are often a major problem for carers. These changes are also of theoretical interest since certain abnormalities may be a direct expression of specific brain pathology. Studying these changes in eating and weight may therefore further our understanding of certain of the pathological processes underlying dementia and suggest new approaches to the management of these problems.